Exploring Ligand-Controlled C2Product Selectivity in Carbon Dioxide Reduction with Copper Metal-Organic Framework Nanosheets - Singh A.K.; Gu L.; Dutta Chowdhury A.; Indra A. (My University, 2025)
The suitable choice of an electrocatalyst is crucial in controlling the selectivity of electrocatalytic CO2reduction products. Herein, we have explored the effect of different ligand environments in 2D metal-organic frameworks (MOFs), viz., copper naphthalenedicarboxylate (Cu-UNDC) and copper benzenedicarboxylate (Cu-UBDC). The change of ligand modulates the structure of the MOFs as well as the electronic environment around the copper center. The variation in the electronic structure and the coordination environment of the active Cu center changes the selectivity toward C2products. In the electrocatalytic process, Cu-UNDC produced 24.3% Faradaic efficiency (FE) for the C2products─far better than that of Cu-UBDC (13.2%). In contrast to electrocatalytic CO2RR, in the presence of light, Cu-UBDC (26.2%) achieved a better FE for the C2products than Cu-UNDC (21.8%). © 2023 American Chemical Society. All rights reserved.